THE RELATHIONSHIP BETWEEN DURATION OF DIABETES AND DIABETES SELF MANAGEMENT BEHAVIORS - Clara Hartuida (JURNAL KEPERAWATAN CIKINI, 2021)
Introduction Diabetes mellitus (DM) is a chronic disease that has an impact on increasing morbidity and mortality. This occurs due to complications arising from chronic hyperglycemia that are not well controlled. Hyperglycemic control can be achieved through the application of daily diabetes self-management behaviors. The factor that might to influence the application of diabetes self-management behavior is the duration of diabetes. The purpose of this research is to identify the relationship between duration of diabetes and self-management behaviors of people with type 2 Diabetes Mellitus. Method A cross-sectional research design was used in this study, and 112 people with type 2 Diabetes Mellitus were recruited. The questionnaire used in this study is The Summary Diabetes Self Care Activity (SDSCA), and Socio-demographic questionnaire. Result The results show the significant relationship between duration of diabetes and self-management behaviors (p value < 0.001), which means that the longer the respondent has DM, the more their self-management behaviors increases. Conclusion Therefore, nurses need to assist people with type 2 diabetes through providing motivation and education about diabetes self-management.